At the crossing-places - Crossley-Holland, Kevin (New York, NY : Arthur A. Levine Books, 2002)
In late twelfth-century England, the thirteen-year-old Arthur goes to begin his new life as squire to Lord Stephen at Holt, where crusaders ready themselves.
Sequel to: The seeing stone.
Keywords: Arthur, King -- Juvenile fiction; Arthur, King -- Fiction; Identity -- Fiction; Magic -- Fiction; Middle Ages -- Fiction; Great Britain -- History -- Richard I, 1189-1199 -- Fiction; Great Britain -- History -- John, 1199-1216 -- Fiction